Producción de semilla de tomate 2.Efecto de la densidad de siembra en la producción y calidad de semilla en dos variedades de tomate (Lycopersicon esculentum Mill) (1978)
An Experiment was carried out at the Experimental Center in Espinal, to study the effect of planting distance on the production and quality of seeds in two varieties of tomatoes grown without stacks, The two varieties were: "Roma" for industrial use and "Glamour" for marketing. For the "Roma" variety the following planting distances were used; 80 and 120 cm, between rows and 30, 45 and 60 cm between plants. "Glamour" tomatoes were seeded at 120 and 160 cm between rows and 30. 50 and 70 cm between plants. For both varieties, especially "Glamour", seed production was lower than normal. With the "Roma" variety, significant differences ocurred only between row distances, with the highest production at 30 x 60 cm. With "Glamour" production differences were observed between both row planting distances. The greatest seed production in the field was obtained with densities of 120 x 130 cm. Low seed and fruit yields with "Glamour" were a result of deficient soils, high temperatures and poor adar'tation to the prostrate system of growth. There was a high correlation between the production of fruits and seeds in both varieties. A moderate density effect was observed on average weight of fruits; however, seed characteristics, such as number of seeds per fruit, viability weight of 100 seeds and size of seedlings were not affected by competence. There was a relationship between the weight of 100 seeds and the plants grown from those seeds. In the "Roma" variety there was a positive correlation between the weight of 100 seeds and the length of the stem. For the "Glamour" variety the relationship was with the length of the stem and the radicule. For the "Roma" variety seed weight was correlated with seed viability. According to the proceeding results, tomatoes seed production does not appear advisable under the environment in which this experiment was carried out.